The winnowing oar - new perspectives in Homeric studies - Tsangalēs, Chrēstos K.; Markantōnatos, Andreas (De Gruyter, 2017)
In the wake of recent advances in the treatment of longstanding problems pertaining to the interpretation of Homeric poetry, this volume brings together cutting-edge research from a cohort of acclaimed scholars on Homer and the Homeric Hymns. The variety
Keywords: Aufsatzsammlung; Festschrift; Homerus